The Crossley ID Guide : Eastern Birds - Crossley, Richard, 1964?- (Book collections on Project MUSE., 2011)
" ... This book changes field guide design to make you a better birder ... The most comprehensive guide : 640 stunning scenes created from 10,000 of the author's photographs ... Lifelike in-focus scenes show birds in their habitats ..."--Page 4 of cover